PHOTOTHERAPY INDUCED HYPOCALCEMIA IN ICTERIC NEWBORNS ATTENDING BIRAT MEDICAL COLLEGE TEACHING HOSPITAL, MORANG, NEPAL - Jha , Chandra bhushan; Rimal , Hem Sagar; Subedi , Ram Bhakta (Journal of Chitwan Medical College, 2022)
Background: Neonatal jaundice is the single most common abnormal physical finding and the cause of morbidity in the first week of life. It is commonly managed by phototherapy. A lesser known, but a potential complication of phototherapy is hypocalcemia. This study was done to determine the prevalence of phototherapy induced hypocalcemia in icteric newborn and to compare it between preterm and term babies. Methods: This was a hospital based cross sectional study carried out in the Department of Pediatrics, Birat Medical College Teaching Hospital from 1st September 2020 to 1st March 2021. This study was performed on 201 icteric newborn that were managed with phototherapy. Serum calcium level was estimated both before initiating phototherapy and after 24 hours of phototherapy. All the data were recorded in the structured proforma. Data was analysed using SPSS version 16. Results: This study was performed on 201 icteric newborn (121 term, 80 preterm). Male babies (n=133; 66.2%) outnumbered the female babies (n=68; 33.8%). The majority of neonates were in the age group of 1-5 days (n=156; 77.6%), with mean age of4.50± 3.39 days.7.9% (16 out of 201) neonates exhibited phototherapy induced hypocalcemia. The prevalence of hypocalcemia in preterm was 10%and term neonates was 6.6%. Conclusions: Hypocalcemia is a significant problem in icteric newborn treated with phototherapy. Hence there is a need for closed monitoring of serum calcium levels. Also the risk is greater in preterm neonates as compared to the term neonates.